Czynniki determinujące konkurencyjność sektora MSP na Pomorzu - Pawłowski, Grzegorz (Determinants of SMEs Competitiveness in Pomerania, 2008)
Contemporary economic development is possible thanks to achievement and exploitation of comparative advantages in particular areas of business activity. A significant part in creation of these advantages is played by small and medium-sized enterprises. Small and medium-sized enterprises in the Pomeranian region are among the best entrenched in the market. Pomeranian SMEs are involved in traditional economic sectors, which are not the leaders of the Knowledge Based Economy. Over two thirds of SMEs have not made any attempts to export their output to external markets but every fourth company is actively, consciously and consistently assessing the needs of its customers. Market processes are a strong stimulus of change and SMEs have to be innovative if they want to maintain their market position. An overwhelming majority of SMEs declared to adopt a gradual path of development or the maintenance of the present position of their company. It is worth to pay attention to a relatively high level of "optimism" of companies, concerning the dynamics of sales. About half of all SMEs were of the opinion that the level of demand corresponds to their production capacity or is slightly smaller. A clear majority of firms declared the intention to retain the number of employees at the current level or to slightly increase it. Nearly half of SMEs in Pomerania are afraid of local competition and only 13.3% of companies are afraid of competition from abroad. All the business support institutions in Pomeranian region should promote the possibility of using structural funds, with particular stress on using easily accessible consultation points; starting up centres of assistance in preparing application documents needed to access the EU structural funds; organize training sessions, courses and informative meetings concerning programmes offered by the EU.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 243-252